2020
DOI: 10.1097/ogx.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization and Risk for Hypertensive Disorders of Pregnancy: Associations With Treatment Parameters

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…In the same paper, further analysis also demonstrated that programmed FET pregnancies were associated with higher incidences of preeclampsia than natural FET pregnancies, which had a comparable risk as fresh IVF pregnancies (50). This nding was again supported by Luke and colleagues (52). These studies proposed that performing FET during a natural cycle or with supplementation of missing hormones, such as relaxin, may potentially reduce the risk of preeclampsia and HDP.…”
Section: Comparison With Existing Literaturementioning
confidence: 77%
See 2 more Smart Citations
“…In the same paper, further analysis also demonstrated that programmed FET pregnancies were associated with higher incidences of preeclampsia than natural FET pregnancies, which had a comparable risk as fresh IVF pregnancies (50). This nding was again supported by Luke and colleagues (52). These studies proposed that performing FET during a natural cycle or with supplementation of missing hormones, such as relaxin, may potentially reduce the risk of preeclampsia and HDP.…”
Section: Comparison With Existing Literaturementioning
confidence: 77%
“…The observed difference between fresh ET and FET may be explained by the absence of a corpus luteum (CL), as suggested by ve recently published cohort studies (32,(49)(50)(51)(52). SC typically develop under the presence of one CL, while the number of CL for IVF pregnancies varies depending on the type of procedure.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The mean fetal weights did not differ in this study, but the percentage of LGA infants was significantly higher in the programmed cycles compared with modified natural cycles (13.5% vs. 12.3%; P ¼ .008). These studies (75,76) taken together suggest the corpus luteum plays a role in aberrant fetal growth and hypertensive disorders of pregnancy.…”
Section: Possible Association Between Frozen Et Lga and Hypertensive Disorders Of Pregnancymentioning
confidence: 96%
“…Women at risk are those with prepregnancy overweight or obesity, pregestational diabetes, and hypertension [30,31]. In addition, advanced maternal age, use of assisted reproductive technology, especially after frozen embryo transfer [32], and multiple pregnancy are relevant further risk factors for the occurrence of eclampsia [31].…”
Section: Introductionmentioning
confidence: 99%